Influence of the Built Environment on Pedestrian Route Choices of Adolescent Girls. (May 2015) - Rodríguez, Daniel A.; Merlin, Louis; Prato, Carlo G.; Conway, Terry L.; Cohen, Deborah; Elder, John P.; Evenson, Kelly R.; McKenzie, Thomas L.; Pickrel, Julie L.; Veblen-Mortenson, Sara
We examined the influence of the built environment on pedestrian route selection among adolescent girls. Portable global positioning system units, accelerometers, and travel diaries were used to identify the origin, destination, and walking routes of girls in San Diego, California, and Minneapolis, Minnesota. We completed an inventory of the built environment on every street segment to measure the characteristics of routes taken and not taken. Route-level variables covering four key conceptual built environment domains (Aesthetics, Destinations, Functionality, and Safety) were used in the analysis of route choice. Shorter distance had the strongest positive association with route choice, whereas the presence of a greenway or trail, higher safety, presence of sidewalks, and availability of destinations along a route were also consistently positively associated with route choice at both sites. The results suggest that it may be possible to encourage pedestrians to walk farther by providing high-quality and stimulating routes.